Human embryonic stem cell derived mesenchymal stromal cell transplantation in rat hind limb injury model - Laurila, Juha P. (2009)
INTRODUCTION: Mesenchymal stromal/stem cells (MSCs) have been used in a wide variety of preclinical experiments and in an increasing number of human clinical trials. Although many of these studies have shown different levels of engraftment, the exact fate of MSCs after transplantation and the tissue response to their engraftment has not been investigated in detail. In the present work we studied the distribution of human MSCs in a rat hind limb ischemic injury model immediately after transplantation and also analyzed the recipient tissue response to transplanted cells. METHODS: We tracked the in vivo fate of the transplanted MSCs utilizing bioluminescence imaging, fluorescence microscopy, and gene/protein expression analysis in rat hind limb ischemia model. We also monitored the viability of transplanted cells by graft vs. recipient expression analysis and determined the angiogenic and proliferative effect of transplantation by histological staining. RESULTS: According to imaging analysis only a small portion of cells persisted for extended period of time at the site of injury. Interestingly, recipient versus graft expression studies showed increased synthesis of rat-origin angiogenic factors and no human-origin mRNA or protein synthesis in transplanted tissues. More importantly, despite the lack of robust engraftment or growth factor secretion the transplantation procedure exerted a significant pro-angiogenic and pro-proliferative effect, which we showed was mediated by angiogenic and mitogenic signaling pathways. DISCUSSION: Our results show an immediate temporal tissue effect in response to MSC transplantation that may represent a novel indirect paracrine mechanism for the beneficial effects of cell transplantation observed in injured tissues.